Genetic analysis and mapping of dwarf gene without yield penalty in a γ-ray-induced wheat mutant - Wang, Qingguo; Xiong, Hongchun; Guo, Huijun; Zhao, Linshu; Xie, Yongdun; Gu, Jiayu; Zhao, Shirong; Ding, Yuping; Liu, Luxiang (Frontiers in Plant Science, 2023)
Plant height is one of the most important agronomic traits that affects yield in wheat, owing to that the utilization of dwarf or semi-dwarf genes is closely associated with lodging resistance. In this study, we identified a semi-dwarf mutant, jg0030, induced by γ-ray mutagenesis of the wheat variety ‘Jing411’ (wild type). Compared with the ‘Jing411’, plant height of the jg0030 mutant was reduced by 7%-18% in two years’ field experiments, and the plants showed no changes in yield-related traits. Treatment with gibberellic acid (GA) suggested that jg0030 is a GA-sensitive mutant. Analysis of the frequency distribution of plant height in 297 F3 families derived from crossing jg0030 with the ‘Jing411’ indicated that the semi-dwarf phenotype is controlled by a major gene. Using the wheat 660K SNP array-based Bulked Segregant Analysis (BSA) and the exome capture sequencing-BSA assay, the dwarf gene was mapped on the long arm of chromosome 2B. We developed a set of KASP markers and mapped the dwarf gene to a region between marker PH1 and PH7. This region encompassed a genetic distance of 55.21 cM, corresponding to a physical distance of 98.3 Mb. The results of our study provide a new genetic resource and linked markers for wheat improvement in molecular breeding programs.